Development of a tonic form of synaptic inhibition in rat cerebellar granule cells resulting from persistent activation of GABAA receptors. - Brickley, S G (1996)
1. To investigate the origin and functional significance of a recently described tonic GABAA receptor-mediated conductance in cerebellar granule cells we have made recordings from cells in cerebellar slices from rats of different ages (postnatal days P4 to P28). 2. During development there was a dramatic change in the properties of GABA-mediated synaptic transmission. The contribution to GABAA receptor-mediated charge transfer from the tonic conductance (GGABA), relative to that resulting from discrete spontaneous postsynaptic currents (sPSCs), was increased from 5% at P7 to 99% at P21. GGABA was reduced by bicuculline, tetrodotoxin and by lowering extracellular Ca2+, and was initially present only in those cells which exhibited sPSCs. 3. At P7 sPSCs were depolarizing, occasionally triggering a single action potential. By P18 the GABA reversal potential was shifted close to the resting potential and GGABA produced a shunting inhibition. Removal of GGABA by bicuculline increased granule cell excitability in response to current injection. 4. This novel tonic inhibition is present despite the low number of Golgi cell synapses on individual granule cells and appears to result from 'overspill' of synaptically released GABA leading to activation of synaptic and extrasynaptic GABAA receptors.